The Avon Longitudinal Study of Parents and Children (ALSPAC): a 2022 update on the enrolled sample of mothers and the associated baseline data [version 1; peer review: 2 approved] - Kate Northstone; Jean Golding; Jon Heron; Abigail Fraser; Daniel Major-Smith; Deborah A. Lawlor (Wellcome Open Research, 2022)
The Avon Longitudinal Study of Parents and Children (ALSPAC) is a prospective birth cohort, based in and around Bristol, UK, established to explore genetic and environmental factors impacting health and development. 14,541 pregnancies were initially recruited from 20,248 eligible pregnancies. As the G1 offspring turned 7 years of age, children from eligible pregnancies who had not been enrolled into the study were invited to take part. The enrolment status of these additional G1 offspring (n=913) has been well-documented. Here we provide an updated description of the ALSPAC G0 mothers study cohort (which includes newly enrolled mothers), their associated pregnancies and the mz data file that defines this cohort. At the time of writing there are 14,833 unique mothers enrolled in ALSPAC, with 15,447 associated pregnancies enrolled. The update to the mz file also includes new variables to assist researchers when using mothers’ data whilst accounting for non-independence between data related to multiple pregnancies (i.e., women with more than one pregnancy in the study).